1994
DOI: 10.1103/physreve.50.r1741
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of deposition growth models in various dimensions: The possible importance of overhangs

Abstract: We present simulation results of deposition growth of surfaces in two, three, and four dimensions for ballistic deposition where overhangs are present, and for restricted solid on solid deposition where there are no overhangs. The values of the scaling exponents for the two models are found to be different, suggesting that they belong to different universality classes

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Without invoking (4) the estimation of α would be hampered by the slow power-law crossover to the asymptotic regime and underestimates of α would be obtained (as discussed above). This crossover would explain the discrepancies between previous estimates of α for BD (κ=0) and the KPZ value [6,4,9].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Without invoking (4) the estimation of α would be hampered by the slow power-law crossover to the asymptotic regime and underestimates of α would be obtained (as discussed above). This crossover would explain the discrepancies between previous estimates of α for BD (κ=0) and the KPZ value [6,4,9].…”
mentioning
confidence: 92%
“…Even when the interfacial dynamics are local, numerical studies have suggested that α is reduced when the bulk structure contains holes: for the ballistic deposition (BD) model values of α=0.42(3) [6] and 0.47(1) [4] were reported in early work on 1+1 dimensional BD, whereas more recent very large-scale simulations [9] yielded an estimate of α=0.45. Although BD is generally accepted as being a realization of KPZ growth, the possibility that a noncompact bulk structure implies a new non-KPZ university class has been raised [9,10].…”
mentioning
confidence: 99%
“…In two dimensions the values of the KPZ systems are not known exactly. There is a large diver-*Electronic address: eytak@post.tau.ac.il † Electronic address: mosh@tarazan.tau.ac.il 3 + 1 0.12 [13] sity of results that range between 0.18 and 0.4 for ␣ and 0.1 and 0.25 for ␤ [16] (these results were obtained by a direct integration of the KPZ equation or the equivalent directed polymer problem). However, it usually accepted that ␣ = ϳ 0.4 and ␤ = 0.24 are the KPZ exponents in 2 + 1 dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical results are consistent with the proposition that RSOS and KPZ models belong to the same universality class, but the situation is more controversial when considering the BD and Eden models.For the KPZ equation in d = 1, the exact values α = 1/2 and β = 1/3 are known [3]. The estimated values obtained by various numerical works on BD in d = 1 for roughness exponent and growth exponent range from α = 0.42 to 0.506 and β = 0.3 to 0.339 [13][14][15][16][17]. Among the results, those obtained by Reis [17] are close enough to the exact KPZ values.…”
mentioning
confidence: 99%